The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5489/cuaj.2383
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with microsurgical spermatic cord denervation for chronic orchialgia at a Canadian centre

Abstract: Introduction: Microsurgical spermatic cord denervation (MSCD) is an effective surgical technique to manage chronic orchalgia, but it has not been readily adopted by Canadian urosurgeons. This paper reviews the early experience of a single urosurgeon in Canada. Methods: Nine consecutive testicular units underwent MSCD over a 24 month period. These patients underwent MSCD after ruling out reversible causes and after a successful diagnostic spermatic cord block. Results: Of these patients, 77% (7/9) had a complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…first reported MSCD in 1978. Good response rates have been reported in multiple studies since that initial experience 467891011121314. Another anatomic study of the nerves in and in proximity to the spermatic cord has identified sensory and autonomic nerve fibers, most of which were found to be sensory and sympathetic nerve fibers, and few parasympathetic nerve fibers in the spermatic cord and surrounding tissues 15.…”
Section: Discussionmentioning
confidence: 95%
“…first reported MSCD in 1978. Good response rates have been reported in multiple studies since that initial experience 467891011121314. Another anatomic study of the nerves in and in proximity to the spermatic cord has identified sensory and autonomic nerve fibers, most of which were found to be sensory and sympathetic nerve fibers, and few parasympathetic nerve fibers in the spermatic cord and surrounding tissues 15.…”
Section: Discussionmentioning
confidence: 95%
“…And it is thought to represent neural changes in the peripheral and central system, which enable persistent stimulation of pain centers in the absence of threshold stimulation. As such, chronic pain syndromes can occur anywhere, including the testicle or the scrotum [20,21]. More complex and centrally located pathologies may also be responsible for the pain, such as musculoskeletal injury, particularly of the lumbosacral region [9].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous groups have published success rates ranging from 77–100% in terms of significant reduction or elimination of pain. 18 , 21 , 22 , 47 , 62 The trifecta nerve complex mentioned in the pathophysiology section above explains the benefit of MDSC in CSP patients. Ligation of the nerves with Wallerian degeneration in the trifecta is likely to provide pain relief or reduction in CSP patients undergoing MDSC.…”
Section: Treatment Algorithm For Chronic Orchialgia or Chronic Scrotamentioning
confidence: 99%